Study protocol for a randomized controlled trial of the RASPERA project: recalling and anticipating specific positive events to boost resilience in adolescents - Eline Loyen; Eline Loyen; Liesbeth Bogaert; Liesbeth Bogaert; David John Hallford; Arnaud D'Argembeau; Filip Raes; Filip Raes (Frontiers Media S.A., 2023)
BackgroundMany stress-related mental health problems, like depression and anxiety, emerge during adolescence, with some recent studies suggesting numbers are increasing. One possible way to reduce adolescents' vulnerability to stress-related mental health problems is to increase their resilience by training them in recalling specific positive memories and anticipating specific positive future events. Therefore, an innovative combi-training (called Positive Events Training; PET) was developed, focusing on the enhancement of the specificity of both past and future positive autobiographical events in adolescents. Its effects on adolescents' resilience and mental wellbeing will be examined.MethodsA cluster randomized controlled trial with a 2 (condition) × 3 (time-point) factorial design was conducted. Classes of adolescents were randomized to either a PET program (intervention) or a CREAtive writing Training (CREAT) program (active control). Both trainings consisted of four sessions of 50 min (one session, weekly, for four consecutive weeks) and were delivered in schools. Before (pre-training, T1), immediately after (post-training, T2), and 2 months after the training (follow-up, T3), participants completed a series of self-report questionnaires. Primary outcomes are resilience and mental wellbeing. Secondary outcomes are positive affect, positive affect regulation and anhedonia. CONSORT criteria for conducting and reporting RCTs will be used.Ethics and disseminationEthical approval was obtained from the Social and Societal Ethics Committee (SMEC) and the study has been preregistered on Open Science Framework (OSF) and ClinicalTrials.gov (Trial registration number: NCT05757180). We plan to develop a free, online, web-based self-directed PET protocol for teachers if the study provides evidence for the effectiveness of the PET program in increasing adolescents' resilience and mental wellbeing, so teachers can deliver the program to future students without the need of professional external trainers.